Polypharmacy in a Belgian cohort of community-dwelling oldest old (80+). Issue 3 (3rd May 2016) - Wauters, Maarten; Elseviers, Monique; Vaes, Bert; Degryse, Jan; Dalleur, Olivia; Vander Stichele, Robert; Van Bortel, Luc; Azermai, Majda
Abstract: Objectives: Polypharmacy is highly prevalent among older people (65+), but little is known on the medication use of the oldest old (80+). This study explores the medication use of the Belgian community-dwelling oldest old in relation to their demographic, clinical and functional characteristics. Methods: Baseline data was used from the BELFRAIL study; a prospective, observational population-based cohort of Belgian community-dwelling patients (80+). General practitioners recorded clinical problems and medications. Medications were coded by the Anatomic Therapeutic Chemical classification. Results: Participants' ( n = 503) mean age was 84.4 years (range 80–102) and 61.2% was female. Median chronic medication use was 5 (range 0–16). Polypharmacy (≥5 medications) was high (57.7%), with excessive polypharmacy (≥10 medications) in 9.1%. Most commonly used medication group were antithrombotics, but also benzodiazepines and antidepressants were frequently consumed. Demographics related to polypharmacy (univariate analysis) were female gender, low education and moderate alcohol use. Age, care dependency and cognitive impairment showed no association with polypharmacy. In multivariate analysis, the predominant association with polypharmacy was found for multimorbidity (OR 1.78, 95% CI 1.5–2.1), followed by depression (OR 3.7, 95% CI 4.4–9.7) and physical activity (OR 0.8, 95% CI 0.7–0.9). Conclusions: Polypharmacy was high among Belgian community-dwelling oldest old (80+). Determinants of polypharmacy were interrelated, but dominated by multimorbidity. On top of the burden of multimorbidity, polypharmacy was independently associated with less physical activity, and with depressive symptoms.